THE COMPLEXITY OF THE HEALTHCARE SYSTEM AND ITS RELATIONSHIP WITH CITIZENS AND INSTITUTIONS: WHAT BALANCE IS POSSIBLE? - Sorrgente, Antonella Eliana (PEOPLE: International Journal of Social Sciences, 2024)
The speech will start with the difficulty of management and interpretation of the regulatory and organisational complexity of a health context (in particular a hospital) and will try to trace a possible mode of interaction between stakeholders and institutions based on the project work developed, with Doctor Franco Milani, for the Executive master’s in strategic management and leadership of health Organizations attended at the University of Pavia during a.a. 2021-2022. The management of the relationship between regulatory and organisational complexity in the healthcare context and the relationship with the patient/citizen is deemed to require i) the implementation of new leadership styles, ii) the dissemination of Non-Technical Skills, iii) the implementation, structured and specific, of participatory processes, so that public action is implemented in a tailor-made way for the need of the community for which it was thought iv) a new mode of communication between stakeholders and institutions so that the ethics of the relationship and communication, transparency and accountability become the pivot of a new mode of interaction.